2013
DOI: 10.2196/mhealth.2688
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Human Resource Gap in Primary Health Care Delivery Systems of Developing Countries With mHealth: Narrative Literature Review

Abstract: BackgroundMobile health (mHealth) has the potential to solve human resource issues in the health care sector. mHealth is of particular interest in developing countries, where widespread mobile networks and access to devices are connecting people like never before.ObjectiveThe aim of this paper was to review published and unpublished literature, field projects, and pilot studies on mHealth usage in overcoming shortage of human health resources in developing countries.MethodsA narrative literature review was und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 12 publications
0
42
0
Order By: Relevance
“…Although the number of studies included in these reviews have been few in number, improvements have been observed in health care service delivery processes [10], behavior change (particularly smoking cessation) [10,11], and use of geographic information systems to support improved health care [12]. In LMIC settings, the mHealth literature is dominated by interventions in maternal and child health and sexual health, with a particular focus on use of mobile phones for data collection [13][14][15]. Braun et al identified 25 studies exploring community health workers' use of mobile technology [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of studies included in these reviews have been few in number, improvements have been observed in health care service delivery processes [10], behavior change (particularly smoking cessation) [10,11], and use of geographic information systems to support improved health care [12]. In LMIC settings, the mHealth literature is dominated by interventions in maternal and child health and sexual health, with a particular focus on use of mobile phones for data collection [13][14][15]. Braun et al identified 25 studies exploring community health workers' use of mobile technology [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies were small scale and of the few that reported outcome evaluations, some demonstrated improvements in quality of care. Goel et al conducted a narrative synthesis of 28 studies to examine the role of mHealth in bridging human resource gaps [15]. The authors found mHealth to be widely used in PHC settings for varying purposes including data collection, health surveillance, health education, supervision, and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…As mobile technologies have proliferated throughout LMICs, their use in a variety of healthrelated activities has been studied [61][62][63][64][65][66][67][68][69][70][71][72]. As rapidly as mobile technology use has grown, the mHealth literature also has rapidly increased.…”
Section: Synthesis Of Ghi Studiesmentioning
confidence: 99%
“…Maternal mortality is decreasing in many countries, yet over 300,000 women still die annually, particularly in low-and middle-income countries (LMICs) [1]. The utilization of mobile health (mHealth) has been proposed as a potential solution to improve maternal health outcomes in LMICs [2][3][4]. There is evidence in a growing body of research that despite indications of positive outcomes, the continued focus of mHealth research on activities and inputs and less on the mechanisms behind program success and failure have contributed to gaps in evidence on the effectiveness on mHealth interventions [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%